Empowering teachers to create learning animation videos with an assessment as learning approach - Rukli, R.; H, Nurhikmah; Nurindah, N. (Universitas Pendidikan Indonesia, 2023)
The technological age dragged other fields to use technology, including video games. As a result, video games are increasingly popular with school children, especially elementary school children. Even though teachers are the front line to divert children's attention from playing games to learning animations, the teacher working group of Rayon 18 South Sulawesi has limitations in making interesting videos even though they have carried out several activities. Therefore, empowering teachers is a solution to apply research results by participating in training to make learning animation videos using the assessment as a learning approach. The activity was attended by 35 elementary school teachers from the rayon for one day with three sessions. The direction of the line of training participants' understanding ability increases where the post-test score is higher than the pre-test. The correlation between questions shows a consistent increase. Likewise, this increases teacher skills in installing applications, applying video applications to create videos, and increasing teacher skills in creating animated learning videos. Teachers feel satisfied receiving the benefits of taking part in training in making learning animation videos. Therefore, teachers can increase creativity by creating learning animation videos so students are more interested and focused on learning.